Identification of Stable Biparental Maize Hybrids - Kumar, P; Gupta, S C (Annals of Arid Zone, 2016)
The biparental hybrids and parental lines were evaluated in four envionrments. The estimates of stability analysis indicatd that additive (cr2 A) and non-additive (cr2 D) gene actions were responsible for expression of days to silking and maturity. tassel length, LAL shelling percentage, biologial yield and grain yield, while non-additive (cr2 D) gene action were pre-dominant for ASL number of leaves per plant and number of leaves above main cob. Hybrids (X2W 3121-1-12 x Pop 30-5040-2). (X2W 3770-2-2-1 x X2,W 3121-1-12), (X,W 8055-2 x X2W 3121-1-12). (X2W 3997- 1-1-1-1 x X,W 8001). (X2W 3048-3-1-2 x X,W 1016-2-3-2). (X2W 3112-1-1-2 x X2W 3048-3-1-2), (X2W 3770-2-2-1 x X2W 3048-3-1-2). (XjW 1629-1-1 x Pop 30-5047-2), (XIW 8055-2 x X\W 8001), (X,W 1629-1-1 X X,W 1016-2-3-2) and (X, W 8052 x Pop 30-5040-2) exhibited suitability under different agro-climatic conditions for grain yield and its contributing and developmental traits. while hybrid (X, W 8052 x X, W 1629- I- I) was appropriate for water stress conditions.